2021
DOI: 10.1186/s12931-021-01750-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for persistent abnormality on chest radiographs at 12-weeks post hospitalisation with PCR confirmed COVID-19

Abstract: Background The long-term consequences of COVID-19 remain unclear. There is concern a proportion of patients will progress to develop pulmonary fibrosis. We aimed to assess the temporal change in CXR infiltrates in a cohort of patients following hospitalisation for COVID-19. Methods We conducted a single-centre prospective cohort study of patients admitted to University Hospital Southampton with confirmed SARS-CoV2 infection between 20th March and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
4
19
0
Order By: Relevance
“… 13 These authors also observed that the risk of these persistent abnormalities was associated with obesity. 13 …”
Section: Discussionmentioning
confidence: 93%
“… 13 These authors also observed that the risk of these persistent abnormalities was associated with obesity. 13 …”
Section: Discussionmentioning
confidence: 93%
“…Elevated levels of IL-10 in severe patients negatively regulates cystatin C, while mild patients have higher levels of this protease inhibitor, used as a prognostic biomarker [ 32 ]. Levels of LDH higher than 750 U/L, together with other factors such as obesity and smoking status, can strongly predict risk of persistent abnormalities on chest X-rays (CXR) [ 34 ]. They also found elevated levels of a number of serum molecules like D-dimer, PCT, CRP, and albumin in severe patients.…”
Section: Association Of Common Blood-based Biomarkers and Covid-19 Se...mentioning
confidence: 99%
“…A few other outcomes were also assessed. One study found that smokers were more likely to have chest X-ray abnormalities 12 weeks after hospitalization, which correlated with longer hospital stays and longer recovery times [ 26 ]. Another study also indicated that smokers may be at risk of longer hospital stays or longer disease duration, but results were not conclusive [ 27 ].…”
Section: Resultsmentioning
confidence: 99%